Traditional Architecture Settings in Housing and Residential Area Governance Based on Local Wisdom in Bali Province - Arna, Md. Andhi Supriatna; Usfunan, Yohanes; Sudantra, I Ketut; Resen, Made Gde Subha Karma (Formosa Journal of Multidisciplinary Research, 2024)
This research uses normative research methods with a statutory approach, historical approach and conceptual approach. The results of this study are The urgency of traditional architectural arrangements in the governance of residential housing based on local wisdom in Bali Province is 1) realizing legal certainty in the implementation of residential housing in Bali Province; 2) realizing housing and residential areas in Bali Province with character; and 3) preserving local wisdom in Bali. Strategies for regulating traditional architecture in the governance of residential housing based on local wisdom in the province of Bali at the present time, including: 1) realizing the change in the status of Bali Province as a special region; 2) adjusting regulations in several fields related to residential housing, spatial planning, land, licensing and building architecture at the central and regional levels of the province of Bali; and 3) supervise the implementation of traditional architectural arrangements in the governance of housing and residential areas based on local wisdom in Bali Province.